Reading Interest Analysis eBook as a Learning Resource for STKIP Muhammadiyah Sampit Students - Hadianur, Muhammad; Elliya, Elliya; Qahfi, Muhamat (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The aims of this research is to describe the interest in reading digital books (e-books) as a learning resource for students of STKIP Muhammadiyah SampitThe sample were students majoring in Economics Education from 2018th until 2021th, it is used a proportional random sampling technique. The number of samples used in this study was 32 students, which was taken from 25% for each class. Data collection technique using a questionnaire. The research data was analyzed using the SPSS statistical program version 16 for windows. The data analysis technique used is descriptive quantitative.The results of this research, there are three categorizations of interest in reading digital books, they are the medium category which is 72% with the number of respondents being 23td students, the high category is 16% with the number of respondents 5th students, and the low category is 13% with the number of respondents 4th students.